2018
DOI: 10.1039/c7nr08797g
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic nanosheets for effective charge transport layers in planar-type perovskite solar cells

Abstract: Herein, solvent-treated bandgap-tunable covalent organic nanosheets (CONs) were prepared via the Stille cross-coupling reaction. These materials are considered useful as interlayers in photovoltaic devices upon the alignment of energy levels between other components. Among various types of solar cells, according to the organic-interlayer study, inverted planar perovskite solar cells (PSCs) are mostly demanded to effectively transport and collect charge carriers due to their high performance. At first, the C-V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…[ 91 ] In order to remedy the above‐mentioned defects, Stille cross‐coupling reaction was adopted by Park et al to prepare CONs with a weak aggregation tendency, as well as an enhanced colloidal stability in organic solvents. [ 92,93 ] The as‐prepared CONs were characterized to display 2D lamellar morphology, which can be regarded as the delaminated COFs. Park and co‐workers found that through a precise control of reaction conditions and monomer combination, the as‐obtained CONs were adjustable on specific surface area, self‐assembled morphology, and molecular planarity.…”
Section: Strategies To Improve the Performances Of Cofs Electrodementioning
confidence: 99%
“…[ 91 ] In order to remedy the above‐mentioned defects, Stille cross‐coupling reaction was adopted by Park et al to prepare CONs with a weak aggregation tendency, as well as an enhanced colloidal stability in organic solvents. [ 92,93 ] The as‐prepared CONs were characterized to display 2D lamellar morphology, which can be regarded as the delaminated COFs. Park and co‐workers found that through a precise control of reaction conditions and monomer combination, the as‐obtained CONs were adjustable on specific surface area, self‐assembled morphology, and molecular planarity.…”
Section: Strategies To Improve the Performances Of Cofs Electrodementioning
confidence: 99%
“…Park and co-workers illustrated in a study the use of a 2D COF prepared by the Stille coupling as a hole transport layer in perovskite solar cells. 207 In device arrangements featuring the 2D COF, an increase in power conversion efficiency of 1% is observed. Generally speaking, the use of 2DFMs in photovoltaics are still only scarcely researched, even though plenty of studies on 3D and layered framework materials exist, still there is a long way to go to reach the full potential of these materials.…”
Section: Applicationsmentioning
confidence: 99%
“…In the line with this research trend, we previously had dedicated our research endeavors to develop new types of effective interlayer materials such as triazine-based two dimensional (2D) covalent organic nanosheets (CONs) for HTLs and highly branched triazine-based porous organic polymers (T-POPs) with alkyl chains for ETLs. [5,6] Each layer showed enhanced charge carrier transport properties, mostly relying on π-π* electronic transitions. Since the surface of ETLs should be smooth for better contact with top electrodes, hyper-branched T-POPs were designed to be more soluble and exhibit less tendency for agglomeration with alkyl chains, in contrast to CON as HTLs.…”
Section: Introductionmentioning
confidence: 99%